2018
DOI: 10.9734/air/2018/41145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sucrose and Boric Acid on in-vitro Pollen Germination of Guava (Psidium guajava) Varieties

Abstract: The Premise of Research: To reproduce, higher plants utilize a unique multicellular microorganism: The male gametophyte, or pollen grain. It is known fact that pollen has a strong impact on physical and biochemical quality of fruit. Pollen germination and pollen tube growth are prerequisites for fertilization and seed development. Information about pollen germination will be helpful in the production of hybrids, which is an important step in a breeding program. In guava, such work on the pollen growth under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Most of the media, for example, those of Prunus laurocerasus (Sulusoglu and Cavusoglu, 2014), Garcinia mangostana (Sutthinon et al, 2018), Triticum aestivum (Turan et al, 2018), and Hydrangea macrophylla, Dichroa febrifuga and their hybrids (Alexander, 2019) have been developed based on the Brewbaker and Kwack medium, which comprises 10% sucrose, 100 ppm boric acid, 300 ppm calcium nitrate, 200 ppm magnesium sulfate, and 100 ppm potassium nitrate (Brewbaker and Kwack, 1963). In fact, in the most essential ones, sucrose or/and boric acid is sufficient; (Sarkar et al, 2018); however, the presence of iron will improve germination or extension (Brewbaker and Kwack, 1963). An optimal medium for pitaya pollen germination is essential for an in vitro pollen study.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the media, for example, those of Prunus laurocerasus (Sulusoglu and Cavusoglu, 2014), Garcinia mangostana (Sutthinon et al, 2018), Triticum aestivum (Turan et al, 2018), and Hydrangea macrophylla, Dichroa febrifuga and their hybrids (Alexander, 2019) have been developed based on the Brewbaker and Kwack medium, which comprises 10% sucrose, 100 ppm boric acid, 300 ppm calcium nitrate, 200 ppm magnesium sulfate, and 100 ppm potassium nitrate (Brewbaker and Kwack, 1963). In fact, in the most essential ones, sucrose or/and boric acid is sufficient; (Sarkar et al, 2018); however, the presence of iron will improve germination or extension (Brewbaker and Kwack, 1963). An optimal medium for pitaya pollen germination is essential for an in vitro pollen study.…”
Section: Introductionmentioning
confidence: 99%
“…The sucrose concentration is an important factor due to promote osmotic balance between pollen and culture media and acts as a source of energy (Sarkar;Sarkar;Vangaru, 2018). Abiotic factors related to incubation conditions, as temperature and presence or absence of light can be considered for the pollen studies.…”
Section: Introductionmentioning
confidence: 99%
“…Guava is a cross-pollinated crop but self-pollination also occurred [8,9]. In guava, studies showed that the distribution of cross-pollination by insects is about 35% and it is said that cross-pollination was the most common form of pollination in guava [10].…”
Section: Introductionmentioning
confidence: 99%